The Impact of The Game of Thrones Series on The Increase in The Number of Tourists in Places Where It Was Filmed - Michal DUDA (Communications of International Proceedings, 2022)
One of the works with the greatest impact on the growth of tourism in places used for filming is the HBO series Game of Thrones. The article presents case studies of several places where the series was filmed, and in the summary, an attempt was made to determine what factors contribute to the tourist success of the locations. In every place where Game of Thrones was filmed, there was an increase in media and tourist interest. It seems that the amount of tourist traffic and the number of visitors is not influenced by the duration of a given location on the screen, but rather by the "originality and spectacular character of the place" - this is the case of the Dark Hedges avenue in Northern Ireland or San Juan de Gaztelugatxe Island in Spain
Keywords: set-jetting; game of thrones; film tourism; hbo; literary tourism; westeros; marketing; tv show